Outcome and health-related quality of life in patients undergoing surgery for spinal metastases and metastatic spinal cord compression - Quraishi, Nasir A. (2020)
Background Surgical treatment for spinal metastases has been shown to improve pain and neurological outcome. However, there remains limited literature on timing of surgery, effects of embolisation, prognostic scoring as well as patient-reported and health-related quality of life (HRQOL) outcome scores in this patient cohort. Furthermore, as most spinal metastases are detected at later stages, the impact of treatment on HRQOL is an important consideration in the choice of treatment.